Jig and fixture Redesign for Main Bearing Housing Component - Asep Indra Komara (P3M Politeknik Negeri Indramayu, 2019)
Main bearing housing is one of the gear transmission product components. The production process of this component needs to be repaired. The repair process is carried out on the fixture construction used today. Redesign is done as one of the solution to improve of the existing fixture design. The measurement results of the products that are machined with the existing fixture are still not in accordance with the requirements of the released product drawing. This is thought to occur because of an error in determining the operating procedur of the machining process that has an impact on the design of the fixture, especially in determining the reference to each machining processes carried out. Therefore, the new fixture needs to be designed so that the resulting product can fit the drawing demands. The repair process is carried out through a gradual study that refers to the methodology of the SME in order to be systematic and structured. Each stage of the design is carried out in detail starting from the study of product analysis, machining analysis, machine analysis, operator analysis and economic analysis. Based on the results of a product analysis study, a new machining process sequence has been produced. The new fixture design has been produced based on this sequence of machining processes. Based on the results of the study, it shows that the results of the redesign of the fixture repair show the conditions that are in accordance with the demands of the product images of the main bearing housing